A review of the pharmacotherapeutic considerations for managing epilepsy in people with autism. (3rd May 2022) - Watkins, Lance V; O'Dwyer, Maire; Shankar, Rohit
ABSTRACT: Introduction: Autism, like other neurodevelopmental disorders (NDDs), has a strong association with epilepsy. There are known common genetic pathways in both autism and epilepsy. There are also specific genetic syndromes associated with both complex epilepsy and the autism phenotype. Areas covered: This review explores the evidence for common genetic etiologies and pathophysiological pathways in relation to both epilepsy and autism. Autism with comorbid epilepsy are associated with a high prevalence of medical and psychiatric comorbidities. This paper discusses how this influences assessment, treatment, and outcomes. The evidence for the treatment of specific seizure types in the context of NDDs is also examined alongside clinical commentary. Expert opinion: Despite the strong association, there is a limited evidence base to support the efficacy and tolerability of anti-seizure medications specifically in autism, with no Level 1 evidence or National Guidance available. Autism and epilepsy should be approached under a NDD model with cautious introduction and titration of anti-seizure medication. Alongside this, there is evidence to support a move toward precision medicine in specific genetic syndromes such as Tuberous Sclerosis Complex and other genetic seizure disorders. The first-line treatments that should be considered for focal seizures include carbamazepine, lamotrigine, and levetiracetam.